Literasi Penyusunan Laporan Keuangan UMKM (Usaha Mikro, Kecil Dan Menengah) Pada Desa di Kecamatan Girsang Sipangan Bolon Kabupaten Simalungun - Purba, Dimita Hemalli Premasari; Situmorang, Duma Rahel; Elisabeth, Duma M.; Silitonga, Ivo M.; Simanjuntak, Wesly A.; Nainggolan, Arison; Simanjuntak, Arthur; Sagala, Lamria; Silalahi, Mulatua P.; Sagala, Farida; Panjaitan, Rike Y.; Ginting, Mitha C.; Simanjuntak, Gracesiela Y.; Junita, Rahel; Purba, Sahala; Pasaribu, Dompak; Mesakh, Januardi; Sipayung, Tri Dharma; Simanjuntak, Rimky M. P.; Siahaan, Septony B.; Napitupulu, Merry Anna; Sembiring, Yosephine N.; Sibarani, Apriani M. (Universitas Methodist Indonesia, 2025)
The Team in collaboration with Parapat Village, Kecamatan Girsang Sipangan Bolon Kabupaten Simalungun helps MSME actors in improving and developing their products through a accounting approach, recording transactions clearly, completely and correctly, so that in the end MSME actors can carry out their business activities. As a benefit of this assistance, in the form of cooperation carried out by two institutions, namely MSME actors will benefit from knowledge and skills to accounting and record transactions that are useful for decision making. For the Service Team, it will add relationships and understanding of community business activities.